Immobilization of ionophore and surface characterization studies of the titanium(III) ion in a PVC-membrane sensor - Rezayi, Majid; Lee, Yook Heng; Kassim, Anuar; Ahmadzadeh, Saeid; Abdollahi, Yadollah; Jahangirian, Hossein (MDPI, 2012)
Novel ionophores comprising various hydroxide and amine structures were immobilized onto poly(vinyl chloride) (PVC) matrices, and these were examined to determine Ti(III) selectivity. To predict the selectivity of Ti(III), a PVC membrane was used to investigate the binding of Ti(III) to c-methylcalix[4]resorcinarene (CMCR). The study showed that the chelating ligand, CMCR, was coordinated selectively to Ti(III) at eight coordination sites involving the oxygen atoms at the interface of the membrane/solution. The membrane was prepared, based on CMCR as an ionophore, sodium tetrakis(4-fluorophenyl) borate (NaTFPB) as a lipophilic ionic additive, and dioctylphthalate (DOP) as a plasticizer. The immobilization of the ionophore and surface characterization studies revealed that the performance of CMCR-immobilized PVC was equivalent to that of mobile ionophores in supported liquid membranes (SLMs). The strengths of the ion-ionophore (CMCR-Ti(OH)(OH2)52+) interactions and the role of ionophores on membranes were studied via UV-Vis, Fourier transform infrared spectroscopy (FT–IR), scanning electron microscopy (SEM) and and X-ray diffraction (XRD).